2007
DOI: 10.1159/000101498
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Relevance: The Fields of Psychosomatics and Psychotherapy in 2006

Abstract: This article reviews several areas of new and interesting development in the fields of psychosomatics and psychotherapy published in the literature during 2006. These areas are: (1) cardiovascular illness and its interplay with depression; (2) risks and predisposing factors in the areas of mental illness and physical illness; (3) new developments in chronic fatigue syndrome, and (4) new or newly explored/modified (psycho)therapies, especially cognitive-behavioral therapy. In addition, an important area of conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…All CFS patients that were selected were required to meet the US Centers for Disease Control and Prevention criteria for CFS (Fukuda, Strauss, & Hickie, 1994). The criterion requiring four out of eight ancillary symptoms to be present for a CFS diagnosis to be made was not used as there is no consistent evidence on the relevance of including these symptoms (Balon, 2007). Fifty‐two CFS patients were thus recruited (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…All CFS patients that were selected were required to meet the US Centers for Disease Control and Prevention criteria for CFS (Fukuda, Strauss, & Hickie, 1994). The criterion requiring four out of eight ancillary symptoms to be present for a CFS diagnosis to be made was not used as there is no consistent evidence on the relevance of including these symptoms (Balon, 2007). Fifty‐two CFS patients were thus recruited (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the training program also appears to have also leaded to a marked reduction of helplessness among parents of afflicted children. This can be seen in the context of a reduction of individual information overload of the patients and their parents [21], especially by augmenting the cognitivebehavioral elements of coping with the disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…All of these patients met the first five US Centers for Disease Control and Prevention criteria for CFS, and none of the exclusion criteria (Fukuda et al , 1994; see Table 1). The sixth criterion was not included as obligatory for including patients as a participant in the study since doubts have been raised on the relevance of the criterion for case diagnosis of CFS (see: Balon, 2007; Prins et al , 2001; Sullivan, Pedersen, Jacks, & Evengard, 2006). As we indicate below, the sixth criterion has been used in rating the severity of CFS patients' fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, however, was the reaction of the interviewers as the study progressed; interviewers working with the psychogenic fatigue group tended to react with significantly more helplessness, disinterest, lack of concentration, impatience, and anger. This reaction could be understood as an actualization of a problem in the interpersonal domain, and may be typical of CFS (see also: Balon, 2007; Huibers & Wessely, 2006). Other studies observed that CFS patients are resistant to therapists that exclusively focus on the psychological side of the problem, as this type of approach does not match the patients' somatic attributions to their condition (Hickie, Lloyd, Wakefield, & Parker, 1990).…”
mentioning
confidence: 99%